Neurobiology of criterion A: self and interpersonal personality functioning - Herpertz, Sabine; Bertsch, Katja; Jeung, Haang (Current opinion in psychology, 2018)
The Criterion A of the DSM-5 Alternative Model of Personality Disorders follows a functional approach to personality disorders which can be effectively related to abnormalities in brain circuits that are involved in processes related to the self and others. While brain circuits related to the self and others highly overlap supporting the notion of inseparable constructs, structural and functional neuroimaging data point to rather specific deviations in brain processes among the various types of personality disorders, with a focus on borderline and antisocial personality disorders. Neurobiological data have shed light on the problem areas of individuals with personality disorders that goes beyond what we know from either patients’ reports or observing their behavior and may open new perspectives on treatment.
Available online 9 September 2017
Gesehen am 08.06.2018